Informal agricultural market channels for food security and poverty reduction: Exploring policy options in Nicaragua - Reyes, Byron A.; Larosa, Francesca; Gómez, Lorena; Buriticá, Alex; Jäger, Matthias; Lundy, Mark M.; Wiegel, Jennifer Rebecca (2023)
The main objective of the data collection was to obtain primary data from three types of actors (intermediaries, wholesalers and retailers) along three value chains (red beans, plum tomatoes, dry/semi-dry cheese) to better understand the opportunities traditional market channels present for food security and poverty reduction for smallholder farmers and poor consumers, and to make policy recommendations oriented to increase the benefits to them. We collected data from main wet markets of three main cities in Nicaragua (Managua, Esteli and Matagalpa).